2019
DOI: 10.1021/acs.biochem.9b00739
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Membranes Influence the Ability of Small Molecules To Inhibit Huntingtin Fibrillization

Abstract: Several diseases, including Alzheimer's disease, Parkinson's disease, and Huntington's disease (HD), are associated with specific proteins aggregating and depositing within tissues and/or cellular compartments. The aggregation of these proteins is characterized by the formation of extended, β-sheet rich fibrils, termed amyloid. In addition, a variety of other aggregate species also form, including oligomers and protofibrils. Specifically, HD is caused by the aggregation of the huntingtin (htt) protein that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 85 publications
4
34
0
Order By: Relevance
“…In a study by Beasley et al, the authors analyzed if the presence of lipid vesicles changed the ability of EGCG or curcumin to modify aggregated htt and affect htt and lipid linkage. They observed that, regardless of the interaction with membrane environment, EGCG prevented htt fibril formation if lipid vesicles were present, inhibiting amyloid formation [ 51 ]; this shows that EGCG is a potential drug candidate for HD treatment and of other conditions involving altered protein aggregation linked to amyloid deposition. A recent study in Drosophila models show that EGCG improves neurodegeneration caused by mutant htt [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Beasley et al, the authors analyzed if the presence of lipid vesicles changed the ability of EGCG or curcumin to modify aggregated htt and affect htt and lipid linkage. They observed that, regardless of the interaction with membrane environment, EGCG prevented htt fibril formation if lipid vesicles were present, inhibiting amyloid formation [ 51 ]; this shows that EGCG is a potential drug candidate for HD treatment and of other conditions involving altered protein aggregation linked to amyloid deposition. A recent study in Drosophila models show that EGCG improves neurodegeneration caused by mutant htt [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the scarcity of in vivo demonstrations, curcumin was reported to impair the misfolding of huntingtin protein, in analogy with the well-established effect on β-amyloid (289,(291)(292)(293)(294)(295).…”
Section: Huntington Diseasementioning
confidence: 97%
“…PFs are formed from proteins implicated in other neurodegenerative diseases, including tauopathy [66], Parkinson's disease [67,68], familial amyloid polyneuropathy [69], and Huntington's disease [70], indicating a common mechanism. Similar to Aβ, tau and α-synuclein (αS) also form PFs with annular, pore-like structures, thereby exerting membrane permeabilization activity [66,67].…”
Section: Pfs Are Present In Other Neurodegenerative Diseasesmentioning
confidence: 99%